Discipleship in Indonesia: The First Decade of Adventist Message (1899-1909) - Chrissutianto, Donny (Klabat Theological Review, 2022)
The first Adventist missionary came to Indonesia at the end of 1899. The first decade of the Adventist work met many challenges and hardships. However, in 1909, the Adventist membership percentage increased sharply if it is compared with the previous and later years. This paper attempts to discover what was the main factor of the successful evangelism from 1899 to 1909. After surveying the information gathered in various periodicals during the first decade of Adventist work in Indonesia, the finding is that discipleship was a significant factor that made the evangelism in Indonesia was successful. Discipleship, including training, needed much time and efforts before it reaped the bountiful harvest. This research also recommends some strengths that can be cultivated and weaknesses that may be avoided to gain better outcomes today. Keywords: Discipleship, Adventist Message, evangelism, Indonesia, adventist missionary Bibliography Bonhoeffer, Dietrich. The Cost of Discipleship. New York, NY: Macmillian, 1963. Conradi, L. R. “God’s mystery to be Quickly Finished,” Union Conference Record, April 15, 1907. Conradi, L. R. “The Dutch General Meeting,” Review and Herald, September 23, 1909. Fulton, J. E. “Java Council Meeting,” Union Conference Record, January 4, 1909. Gates, E. H. “Malaysia Mission,” Union Conference Record, October 1, 1901. Gates, E. H. “Our Work in Sumatra,” Review and Herald, March 26, 1908. Gates, E. H. Review and Herald, March 26, 1908. G., “The Cross,” Australasian Signs of the Times, July 11, 1904. Jones, A. T. “Consecrations of our Means to Service,” Union Conference Record, May 15, 1903. Jones, G. F. “In Sumatra,” Review and Herald, October 31, 1912. Mills, Nettie. “An Interesting Occasion in Singapore,” Union Conference Record, August 24, 1908. Munson, R. W. “Brother Immanuel, the Battak,” Union Conference Record, September 15, 1905. Munson, R. W. “Greetings from Sumatra,” Union Conference Record, October 15, 1903. Munson, R. W. “Netherlands Indies,” Review and Herald, May 8, 1900. Munson, R. W. “Our Work in Sumatra,” Review and Herald, April 28, 1904. Munson, R. W. “Padang, West Coast Sumatra, East Indies,” RH, May 19, 1903. Munson, R. W. “Sumatra,” Review and Herald, November 16, 1905. Munson, R. W. “The Island of Sumatera,” Review and Herald, December 1, 1900. Munson, R. W. “The Island of Sumatera,” Union Conference Record, December 1, 1900. Munson, R. W. “The Work in Malaysia,” Review and Herald, September 2, 1902. Munson, R. W. Union Conference Record, June 24, 1907. Munson, R. W. Union Conference Record, September 15, 1905. Munson, Review and Herald, November 16, 1905. Nordstrom, A. “A letter from Java,” Union Conference Record, March 23, 1908. Olsen, O. A. “New Zealand,” Union Conference Record, February 24, 1908. Patterson, W. R. “Learning by Suffering,” Australasian Signs of the Times, April 29, 1907. Pringle, Robert. Understanding Islam in Indonesia: Politics and Diversity. Honolulu, HI: University of Hawaii, 2010. Rogers, H. E. Statistical Report of Seventh-day Adventist Conferences, Missions, and Institutions. Takoma Park, Washington D. C: General Conference of Seventh-day Adventist, 1909. Taylor, W. L. “A Contended Mind,” Australasian Signs of the Times, June 8, 1908. Tunheim, Petra. “Back to Pagoengsen,” Union Conference Record, February 15, 1909. Tunheim, Petra. “House-to-House Work in Java,” Union Conference Record, June 1, 1908. Tunheim, Petra. “Java Mission,” Union Conference Record, September 7, 1908. Volpe, Medi Ann. Rethinking Christian Identity: Doctrine and Discipleship. Chichester, WS: Wiley-Blackwell, 2013. Walker, Marcelia A. “Letter from Ezekiel Of Batakland,” Union Conference Record, August 30, 1909. Walker, Marcelia A. “Sumatra,” Review and Herald, June 2, 1903. Wantzlick, G. A. “Sumatra,” Review and Herald, June 25, 1908. Wantzlick, G. A. “Sumatra,” Union Conference Record, September 7, 1908. White, Ellen G. “The Restoration of Peter,” Australasian Signs of the Times, August 23, 1909. White, Ellen G. “To Every Man His Work,” Australasian Signs of the Times, February 1, 1909. White, Ellen G. “Words of Counsel,” Union Conference Record, November 15, 1903.